Educational web resources as an essential part of the English learning process - Dandan, Shi; Fazlyeva, Zulfiia Kh.; Samarkina, Nadezhda O.; Carlson, Charles (Universidade Estadual Paulista, 2021)
The article discusses the use of educational web resources in the process of learning English. The authors present different web resources to teach English which have proved to be an effective source in second language acquisition. Web resources help to improve the foreign language perception, to study grammar rules and correct pronunciation, to get acquainted to the culture of the target language and to heighten the interest of learning a foreign language. The advantage of using web resources lies behind the didactic principle of visibility. Visual representation of material proves to be the most important tool to better perceive information and to overall motivate children to stay focused on the task, while creating a natural language environment. As a result of this analysis the authors strongly agree on the benefits of using authentic web resources in teaching English. The analysis has also shown a complete correlation between the use of Internet technologies and course content mastering.